Microstructure, Macrosegregation, and Thermal Analysis of Direct Chill Cast AA5182 Aluminum Alloy - Jamaly, N.; Haghdadi, N.; Phillion, A.B. (Springer, 2015)
The variation in microstructure, macrosegregation, and solidification behavior during aluminum alloy Direct Chill casting is investigated with respect to geometry. Optical microscopy, energy dispersive analysis and differential scanning calorimetry were employed to study the grain size evolution, distribution of alloying elements and solidification sequence across the cross-section of DC cast AA5182 aluminum alloy. The results show: (1) grain size increases from the surface to center of the ingot, corresponding to a decrease in the heat extraction rate; (2) there is a considerable macrosegregation of Mg, Mn and Cr, with Mg showing negative segregation at the center and positive segregation at the surface, Mn showing negative segregation both at center and surface and positive segregation elsewhere, and Cr showing positive segregation at the center and negative segregation at the surface; (3) thermal analysis of the as cast AA5182 also demonstrated that the solidus and the reaction temperatures vary as a function of position due to the local chemical composition and cooling rate. These findings, which show the interconnectivity of grain size, segregation and solidification sequence, are useful in further analysis of the DC casting process and in predicting casting-related defects, specifically hot tear formation.
Keywords: Direct chill casting; Aluminum alloys; Grain size; Macrosegregation; Differential scanning calorimetry